Role of recombinant ecotropic and polytropic viruses in the development of spontaneous thymic lymphomas in HRS/J mice. - Thomas, C Y (1984)
The biological and genetic characteristics of murine leukemia viruses (MuLV) derived from leukemic and normal HRS/J mice were studied. T1-oligonucleotide fingerprinting and mapping of viral RNAs from unpassaged isolates revealed the presence of complex mixtures of viral genomes. MuLV that were purified by endpoint dilution were genetically heterogeneous. Thus, endogenous retroviral sequences expressed in the tissues of HRS/J mice readily recombined with one another. Furthermore, the regular recovery of recombinant ecotropic MuLV suggested reciprocal in vivo complementation of a genetic defect(s) in each of the endogenous ecotropic proviruses Emv-1 and Emv-3. Some recombinant ecotropic viruses contained sequences in the p15E-U3 region that were not derived from Emv-1 and Emv-3 but were found in recombinant polytropic HRS/J viruses. Finally, comparison of the genetic structures of leukemogenic and nonleukemogenic MuLV of this strain implied that the oncogenic phenotype of these MuLV is encoded within env or the U3 region of the genome or both. Our results are consistent with a stepwise convergent evolution of recombinant MuLV in vivo in individual HRS/J mice. Ultimately, this process of selection results in formation of leukemogenic polytropic viruses.